Politikai tiltakozás mint az új politikai kultúra eleme: Magyarország, Szlovénia, Szlovákia (Szociológiai Szemle, 2024)
The study is based upon a survey of leading dailies and weeklies in Hungary, Slovakia and Slovenia regarding their news on protest politics in these countries in 1993. After a short introduction in the traditions of protest, at the scope and methode of analysis, the results on the size, goal, organization and social background of protest will be analyzed. As a preliminary result, existence of differentiated, new protest cultures is documented based upon the new framework of opportunities for mobilizing in the post communist democracy. Characteristic differences of the three countries protest cultures are there, but there are also some common traits of East Central European protests compared with the rather violent mass mobilizations in former Soviet Union and Yugoslavia.